Analisa Perbandingan Metode Certainty Factor dan Teorema Bayes untuk Mendiagnosa Penyakit Cacar Ular - Yusri Rahmi (Bulletin of Information System Research, 2024)
Health is one of the most important cores of life. Skin is the outer layer that covers the body. However, skin diseases often occur in unhealthy skin. Unhealthy skin can easily become infected with viruses. Especially the shingles virus (Herpes Zoster). The shingles virus does not depend on age, anyone can be infected with shingles (Herpes Zoster). Snake pox is very dangerous. Technology, which is developing so rapidly at the moment, is widely used in the field of Artificial Intelligence. Expert systems try to find satisfactory solutions as an expert would. Such as providing an explanation of the steps that must be taken and providing reasons for the suggestions and conclusions found. Based on the problems above, it is necessary to create an expert system that can help the public in diagnosing smallpox, including shingles. In this research, the Certainty Factor method and Bayes' Theorem method were used for comparison and the accuracy of each method was later analyzed. The system will track every symptom experienced by the patient. And then the system will match the existing rules. The expert system that is built is expected to speed up the results of diagnosing the type of disease suffered by the patient. So it can provide fast diagnostic results and appropriate treatment.